A new genus of Grapholitini from Africa related to Thaumatotibia (Lepidoptera, Tortricidae) - Timm, Alicia E. (Pensoft Publishers, 2014)
Abstract. Thaumatovalva gen. n. is described and illustrated from the Afrotropical region. As currently defined the genus includes four species: T. deprinsorum sp. n. from the Democratic Republic of Congo; T. albolineana sp. n. (type species) from the Democratic Republic of Congo; T. spinai (Razowski & Trematerra), comb. n., from Ethiopia and Nigeria; and T. limbata (Diakonoff), comb. n., from the Seychelles and Kenya. Thaumatovalva limbata has been reared from the fruit of Cordia somaliensis Baker and C. monoica Roxb. (Boraginaceae) in Kenya. Although structures of the male and female genitalia are extremely similar among three of the four species, male secondary scales on the under surface of the hindwing easily distinguish them.